The Restricted Six-Body Problem with Stable Equilibrium Points and a Rhomboidal Configuration - M. A. R. Siddique; A. R. Kashif (Advances in Astronomy)
We explore the central configuration of the rhomboidal restricted six-body problem in Newtonian gravity, which has four primaries mi (where i=1,…4) at the vertices of the rhombus a,0, −a,0, 0,b, and 0,−b, respectively, and a fifth mass m0 is at the point of intersection of the diagonals of the rhombus, which is placed at the center of the coordinate system (i.e., at the origin 0,0). The primaries at the rhombus’s opposite vertices are assumed to be equal, that is, m1=m2=m and m3=m4=m˜. After writing equations of motion, we express m0,m, and m˜ in terms of mass parameters a and b. Finally, we find the bounds on a and b for positive masses. In the second part of this article, we investigate the motion and different features of a test particle (sixth body m5) with infinitesimal mass that moves under the gravitational effect of the five primaries in the rhomboidal configuration. All four cases have 16, 12, 20, and 12 equilibrium points, with case-I, case-II, and case-III having stable equilibrium points. A significant shift in the position and the number of equilibrium points was found in four cases with the variations of mass parameters a and b. The regions for the possible motion of test particles have been discovered. It has also been observed that as the Jacobian constant C increases, the permissible region of motion expands. We also have numerically verified the linear stability analysis for different cases, which shows the presence of stable equilibrium points.